Engineering Stacks of V‐Shaped Polyaromatic Compounds with Alkyl Chains for Enhanced Emission in the Solid State. (27th April 2016) - Sekiguchi, Shoya; Kondo, Kei; Sei, Yoshihisa; Akita, Munetaka; Yoshizawa, Michito
Abstract: A V‐shaped bisanthracene derivative with three butyl groups formed two types of emissive solids that display bluish green and blue fluorescence (ΦF =72 and 32 %, respectively), depending on the preparation conditions. The crystal and powder X‐ray analyses reveal that the highly emissive solid adopts a head‐to‐head arrangement with discrete stacks of the anthracene moieties, whereas the moderately emissive solid adopts a head‐to‐tail arrangement without the stacks. The obtained molecular arrangements are transformed by thermal stimuli accompanying the change in fluorescence. Furthermore, large enhancements of dye emissions (12–45‐fold) through highly efficient host–guest energy transfer were achieved in the solid state by adding minute amounts of various fluorescent dyes (e.g. rubrene and Nile red) to the V‐shaped compound.